Plant conformable electrode for mimosa soft robotics - Cai, Lingfeng (Nanyang Technological University, 2020)
Soft robots with high degree of compliance can easily deform to delicate task set-tings and unstructured environments, realizing more adaptive and comfort inter-faces for human-machine and human-environment. Since soft robots are made with materials with moduli similar to soft biological matters and capable of auton-omous movements, scientists have been seeking insights from the nature due the excellent structural and functional capabilities. Most of the design inspiration for soft robots come from animals, such as cephalopod mollusks, because they have no rigid body structure and yet, they can perform sophisticated tasks and move around swiftly. However, very limited studies on plant-based soft robots are pre-sent, because as compared to animals, plants do not possess mobility and fast in-teractions with environmental changes. Nevertheless, there are still some plants demonstrating fast movements, such as insectivorous flytrap trapping down small bugs and “shy” mimosa folding its leaves upon touch. The mechanisms behind these fast movements in plants could also generate new design concepts for soft robots.